Long-Term Exposure of Early-Transformed Human Mammary Cells to Low Doses of Benzo[a]pyrene and/or Bisphenol A Enhances Their Cancerous Phenotype via an AhR/GPR30 Interplay - Donini, Caterina F.; El Helou, Myriam; Wierinckx, Anne; Győrffy, Balázs; Aires, Sophie; Escande, Aurélie; Croze, Séverine; Clezardin, Philippe; Lachuer, Joël; Diab-Assaf, Mona; Ghayad, Sandra E.; Fervers, Béatrice; et al. (Frontiers in Oncology, 2020)
It is of utmost importance to decipher the role of chronic exposure to low doses of environmental carcinogens on breast cancer progression. The early-transformed triple-negative human mammary MCF10AT1 cells were chronically (60 days) exposed to low doses (10−10 M) of Benzo[a]pyrene (B[a]P), a genotoxic agent, and/or Bisphenol A (BPA), an endocrine disruptor. Our study revealed that exposed MCF10AT1 cells developed, in a time-dependent manner, an acquired phenotype characterized by an increase in cancerous properties (anchorage independent growth and stem-like phenotype). Co-exposure of MCF10AT1 cells to B[a]P and BPA led to a significantly greater aggressive phenotype compared to B[a]P or BPA alone. This study provided new insights into the existence of a functional interplay between the aryl hydrocarbon receptor (AhR) and the G protein-coupled receptor 30 (GPR30) by which chronic and low-dose exposure of B[a]P and/or BPA fosters the progression of MCF10AT1 cells into a more aggressive substage. Experiments using AhR or GPR30 antagonists, siRNA strategies, and RNAseq analysis led us to propose a model in which AhR signaling plays a “driver role” in the AhR/GPR30 cross-talk in mediating long-term and low-dose exposure of B[a]P and/or BPA. Retrospective analysis of two independent breast cancer cohorts revealed that the AhR/GPR30 mRNA expression signature resulted in poor breast cancer prognosis, in particular in the ER-negative and the triple-negative subtypes. Finally, the study identified targeting AhR and/or GPR30 with specific antagonists as a strategy capable of inhibiting carcinogenesis associated with chronic exposure to low doses of B[a]P and BPA in MCF10AT1 cells. Altogether, our results indicate that the engagement of both AhR and GPR30 functions, in particular in an ER-negative/triple-negative context of breast cells, favors tumor progression and leads to poor prognosis.